Análise da eficácia da canela (Cinnamomum Verum) na redução dos níveis glicêmicos de pessoas com diabetes Mellitus tipo 2: ensaio clínico aleatorizado - Lira Neto, José Claudio Garcia (2020)
This study aimed to analyze the effectiveness of cinnamon (Cinnamomum verum) in reducing blood glucose levels in people with type 2 diabetes mellitus, compared with placebo. It is a randomized, triple-blind, placebo-controlled clinical trial, developed in five Basic Health Units, in the city of Parnaíba - PI. The study population consisted of adults and the elderly, of both sexes, diagnosed with type 2 diabetes mellitus. After due calculations, the sample size was 154 people. Inclusion criteria were people using oral antidiabetics, with HbA1c ≥ 6.0%; and the exclusion criteria: people with allergies to cinnamon, using insulin, or diagnosed with severe complications that could compromise the analysis. Participants were divided into two groups (experimental and control) and randomized by a computer program. The allocation was made 1: 1 in parallel groups, according to the HbA1c values. The patients in the experimental group received bottles containing capsules with cinnamon and were instructed to take three grams per day, for 90 days. Those in the control group received bottles containing capsules identical to those of the experimental group, but with microcrystalline cellulose (placebo), and were instructed to take the same number of capsules per day, for 90 days. Socioeconomic, clinical, lifestyle-related, laboratory and anthropometric variables were assessed. The t-test was used to compare the means of the numerical variables, and the chi-square test was used to compare the distributions in the categories of the two groups. The final sample consisted of 140 people, the majority of whom were female (69%), brown (57%), and had an average age of 60 years. After 90 days, the mean fasting venous blood glucose decreased by 10 mg / dL in the experimental group and increased by 21 mg / dL in the control group (p = 0.001). HbA1c values fell by 0.2% in the cinnamon group and increased by 0.4% in the placebo group (p = 0.001). Statistically significant reductions were also observed in triglyceride levels and HOMA-IR index, in the experimental group. Cinnamon, in the concentration offered, proved to be effective in reducing glycemic levels. However, it is not yet possible to make generalizations, since the analyzes performed can be influenced by numerous variables. It is recommended that other studies be carried out, as well as the evaluation of the cost-effectiveness of the intervention.